Towards Predictable Datacenter Networks - Ballani, Hitesh; Karagiannis, Thomas; Rowstron, Ant; Costa, Paolo (2011)
The shared nature of the network in today's multi-tenant datacenters implies that network performance for tenants can vary significantly. This applies to both production datacenters and cloud environments. Network performance variability hurts application performance which makes tenant costs unpredictable and causes provider revenue loss. Motivated by these factors, this paper makes the case for extending the tenant-provider interface to explicitly account for the network. We argue this can be achieved by providing tenants with a virtual network connecting their compute instances. To this effect, the key contribution of this paper is the design of virtual network abstractions that capture the trade-off between the performance guarantees offered to tenants, their costs and the provider revenue. To illustrate the feasibility of virtual networks, we develop Oktopus, a system that implements the proposed abstractions. Using realistic, large-scale simulations, and an Oktopus deployment on a 25-node, two-tier testbed, we demonstrate that the use of virtual networks yields significantly higher and more predictable tenant performance. Further, using a simple pricing model, we find that our abstractions can reduce tenant costs by up to 74% while maintaining provider revenue neutrality.